Tox: a multifunctional transcription factor and novel regulator of mammalian corticogenesis. (20th December 2014) - Artegiani, Benedetta; de Jesus Domingues, Antonio M; Bragado Alonso, Sara; Brandl, Elisabeth; Massalini, Simone; Dahl, Andreas; Calegari, Federico
Abstract Major efforts are invested to characterize the factors controlling the proliferation of neural stem cells. During mammalian corticogenesis, our group has identified a small pool of genes that are transiently downregulated in the switch of neural stem cells to neurogenic division and reinduced in newborn neurons. Among these switch genes, we found Tox, a transcription factor with hitherto uncharacterized roles in the nervous system. Here, we investigated the role of Tox in corticogenesis by characterizing its expression at the tissue, cellular and temporal level. We found that Tox is regulated by calcineurin/Nfat signalling. Moreover, we combined DNA adenine methyltransferase identification (DamID) with deep sequencing to characterize the chromatin binding properties of Tox including its motif and downstream transcriptional targets including Sox2, Tbr2, Prox1 and other key factors. Finally, we manipulated Tox in the developing brain and validated its multiple roles in promoting neural stem cell proliferation and neurite outgrowth of newborn neurons. Our data provide a valuable resource to study the role of Tox in other tissues and highlight a novel key player in brain development.